A solidified lepidolite slag cementitious material and its preparation method and application

By curing lithium cloud mother residue gel material, using nano -inorganic resin and rare earth salts to form a stable complex and nano -microphone structure, solve the problem of solid locks of heavy metals such as lithium cloud mother scum, 铍, and other heavy metals. Realize the effectiveness of resource utilization and efficient environmental protection.

CN118545938BActive Publication Date: 2025-01-24HUAZHU LVJIAN (BEIJING) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410465021.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-17
Publication Date
2025-01-24
Estimated Expiration
2044-04-17

AI Technical Summary

Technical Problem

The residual amount of heavy metals such as thallium and beryllium in lithium mica slag is high, resulting in limited storage and absorption and utilization, and the activity of these elements is significantly improved, causing ecological and environmental hazards.

Method used

The cured lithium cloud -mother slag gel material is used, and components such as nano -inorganic resin, rare earth salt and nano -pink powder are formed to form a stable complex and nano -microphole structure, physical and chemical solid lock harmful elements.

Benefits of technology

It can effectively stabilize and lock more than 99% of toxic and harmful elements such as thallium and beryllium in lepidolite slag, reduce their activity and toxicity in the environment, realize resource utilization, and prepare high value-added green building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118545938B_ABST
    Figure CN118545938B_ABST
Patent Text Reader

Abstract

The present invention provides a solidified lithium mica slag cementitious material and a preparation method and application thereof, belonging to the technical field of solid waste treatment and utilization. The cementitious material of the present invention uses lithium slag as a raw material, can effectively and stably lock more than 99% of toxic and harmful elements such as thallium and beryllium in the lithium mica slag, and utilize the harmless lithium mica slag as a resource to prepare high-added green building materials products, eliminate the serious damage of lithium mica slag to the local ecological environment, reduce the environmental protection cost of extracting lithium from mica to prepare lithium carbonate, and enable the lithium extraction industry chain of lithium mica to develop healthily and sustainably.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste treatment and utilization, and in particular to a solidified lepidolite slag gelling material and a preparation method and application thereof. Background Art

[0002] The leached slag in the lithium mica industry chain has a high residual amount of heavy metals such as thallium and beryllium. Due to the principle of element affinity, lithium ores such as lithium mica are often accompanied by thallium and beryllium minerals, which makes the leaching toxicity of thallium and beryllium elements (a type of pollutant) in the lithium mica slag exceed the national standard, resulting in severe restrictions on the storage and disposal of lithium mica slag. In the smelting process of lithium ore, such as sodium chloride pressure cooking process, roasting water leaching process, high acid leaching process, etc., the lattice structure of thallium and beryllium minerals is destroyed, which significantly increases the activity of thallium and beryllium elements in the lithium mica slag; thallium, beryllium and their compounds are highly toxic and will cause great harm to the local ecological environment. The difficulty in handling lithium mica slag has seriously affected the normal development of the mica lithium extraction industry chain and has become an urgent problem that cannot be avoided. Summary of the invention

[0003] The purpose of the present invention is to provide a solidified lepidolite slag gelling material and a preparation method and application thereof, which can effectively and stably lock thallium, beryllium and other toxic and harmful elements in the lepidolite slag and utilize the harmless lepidolite slag as a resource.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The invention provides a solidified lepidolite slag gelling material, which comprises 20-35% of a liquid component and 65-80% of a powder component which are packaged independently, based on a total mass fraction of 100%.

[0006] Based on the total mass fraction of the liquid component being 100%, the liquid component comprises: 96.3-97.9% of nano inorganic resin, 0.5-1% of coupling agent, 1.5-2.5% of lanthanum cerium rare earth salt and 0.1-0.2% of nano yttrium powder;

[0007] Based on the total mass fraction of the powder components being 100%, the powder components include: 30-35% high-calcium fly ash, 40-45% high-calcium slag powder, 8-16% sawdust, 8-16% brick powder and 1-1.5% water reducer;

[0008] The raw materials for preparing the nano inorganic resin include lithium slag, nano modifier and alkali activator.

[0009] Preferably, in terms of mass percentage, the nano modifier includes 10-30% nano silicon dioxide and 70-90% nano aluminum oxide.

[0010] Preferably, the alkaline activator comprises 10-15% sodium silicate solution, 25-30% sodium hydroxide and 60% water.

[0011] Preferably, based on a total mass fraction of 100%, the raw materials for preparing the nano inorganic resin include 40-60% lithium slag, 5-10% nano modifier and 30-55% alkali activator.

[0012] Preferably, the preparation method of the nano inorganic resin comprises: grinding lithium slag, adding a nano modifier and an alkali activator in sequence, and dissolving them to obtain the nano inorganic resin.

[0013] Preferably, the dissolution pressure is 0.3 MPa, the temperature is 250° C., and the time is 8 to 10 h; and the grinding is performed until the particle size of the lithium slag is 1200 mesh.

[0014] Preferably, the coupling agent is aminosilane powder, and the particle size of the aminosilane powder is 1200-2000 mesh;

[0015] The lanthanum-cerium rare earth salt comprises lanthanum chloride and cerium chloride, the mass ratio of the lanthanum chloride to the cerium chloride is 2 to 3:1, and the particle size of the lanthanum-cerium rare earth salt is 400 to 600 meshes;

[0016] The nano yttrium powder comprises yttrium oxide; the purity of the nano yttrium powder is 99.99% and the particle size is 50-100nm.

[0017] Preferably, the calcium content of the high calcium fly ash is greater than 25wt%, and the particle size is 5000-8000 mesh;

[0018] The high calcium slag powder is obtained by grinding 95 slag powder; the calcium content of the high calcium slag powder is 10-30wt%, and the particle size is 5000-8000 mesh;

[0019] The saw mud is obtained by grinding granite, and the particle size of the saw mud is 5000-8000 mesh;

[0020] The brick powder is obtained by grinding red base brick, and the particle size of the brick powder is 5000-8000 mesh;

[0021] The water reducer is a naphthalene-based water reducer.

[0022] The present invention provides application of the solidified lepidolite slag cementitious material described in the above technical solution in building materials.

[0023] Beneficial effects of the present invention:

[0024] The gelling material of the present invention contains lanthanum cerium rare earth salt, and the lanthanum cerium element has a high coordination ability and can form a stable complex; when the lanthanum cerium rare earth salt contacts metal ions such as beryllium and thallium, their electron cloud structure can interact with the electron cloud of the metal ions to form a coordination bond, thereby forming a complex, and this complex usually has a lower solubility and a higher stability, making it more difficult for metal ions such as beryllium and thallium to dissolve and release in the environment, thereby achieving the passivation complexation of beryllium and thallium metal. Further, the 3+ oxidation state of the lanthanum cerium series rare earth elements is the most common valence state, and in this valence state, they have a higher charge density and more unpaired electrons, so that they can form a stronger coordination bond with the metal ions. The formation of this coordination bond allows toxic and harmful elements such as beryllium and thallium to be stably fixed in the complex of the rare earth element, thereby reducing its activity and toxicity in the environment.

[0025] The gelling material of the present invention can physically lock harmful elements through nano-micropores: during the formation process of the gelling material, when the liquid component and the solid component undergo an alkali excitation reaction, the rare earth yttrium generates yttrium compound crystals during the reaction. The crystal structure determines the nano-micropore structure of the material during the formation process and has a template effect on the formation of nano-micropores. The crystal growth process is used to form nanoscale channels to generate nano-micropores with a size of 10 to 20 nm similar to a honeycomb, which can confine toxic and harmful elements such as beryllium and thallium into the micropores and effectively lock them at the physical level.

[0026] The cementitious material of the present invention can anchor harmful elements through the electron balance of silicon, aluminum and oxygen: the silicon and aluminum active substances in the cementitious material form a stable tetrahedral structure with oxygen under the action of an alkali activator, with four electrons on the periphery of silicon and only three electrons on the periphery of aluminum. Therefore, when the electrons of the silicon-oxygen bond reach a balance, the aluminum-oxygen bond cannot be balanced. Aluminum needs to take an electron from other metal ions to balance the aluminum-oxygen bond. The metal ions such as beryllium and thallium whose electrons are taken away form covalent bonds with aluminum to achieve stable chemical anchoring.

[0027] Silicon, aluminum, oxygen and metal ions providing covalent electrons in the solidified lepidolite slag cementitious material of the present invention jointly form a stable tetrahedron with high strength. Therefore, the cementitious material can solidify toxic and harmful elements such as beryllium and thallium in the lepidolite slag and generate a strength body with a compressive strength of 30 to 40 MPa (C30 to C40). The strength body can be used to prepare various prefabricated concrete components, dry-mixed mortar and other green building materials. The strength, impermeability, corrosion resistance and freeze-thaw resistance of the green building material are all better than those of traditional concrete, while the cost is lower than that of traditional concrete, and the green building material has high economic value.

[0028] The gelling material of the present invention uses lithium slag as a raw material, can effectively and stably lock more than 99% of toxic and harmful elements such as thallium and beryllium in the lithium mica slag, and utilize the harmless lithium mica slag as a resource to prepare high-added green building material products, eliminate the serious damage of lithium mica slag to the local ecological environment, reduce the environmental protection cost of extracting lithium from mica to prepare lithium carbonate, and enable the lithium extraction industry chain of lithium mica to develop healthily and sustainably. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the gelling material prepared in Example 1;

[0030] Figure 2 The test results of raw lithium slag;

[0031] Figure 3 This is the test result of the cementitious material of Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The invention provides a solidified lepidolite slag gelling material, which comprises 20-35% of a liquid component and 65-80% of a powder component which are packaged independently, based on a total mass fraction of 100%.

[0033] Based on the total mass fraction of the liquid component being 100%, the liquid component comprises: 96.3-97.9% of nano inorganic resin, 0.5-1% of coupling agent, 1.5-2.5% of lanthanum cerium rare earth salt and 0.1-0.2% of nano yttrium powder;

[0034] Based on the total mass fraction of the powder components being 100%, the powder components include: 30-35% high-calcium fly ash, 40-45% high-calcium slag powder, 8-16% sawdust, 8-16% brick powder and 1-1.5% water reducer;

[0035] The raw materials for preparing the nano inorganic resin include lithium slag, nano modifier and alkali activator.

[0036] The solidified lepidolite slag gelling material provided by the present invention comprises 20-35% of liquid components, more preferably 25-30%; based on the total mass fraction of the liquid components being 100%, the liquid components comprise 96.3-97.9% of nano inorganic resin, preferably 96.5-97.5%, more preferably 97.0%.

[0037] In the present invention, based on the total mass fraction of the nano inorganic resin being 100%, the raw materials for preparing the nano inorganic resin preferably include 40-60% lithium slag, 5-10% nano modifier and 30-55% alkali activator, and more preferably 45-55% lithium slag, 6-8% nano modifier and 35-50% alkali activator.

[0038] The present invention has no special limitation on the composition and source of the lithium slag, and the lithium slag can be obtained from the lithium extraction industry chain of lepidolite in a manner well known in the art.

[0039] In the present invention, the nano modifier comprises 10-30% nano silicon dioxide and 70-90% nano aluminum oxide, more preferably 15-25% nano silicon dioxide and 75-85% nano aluminum oxide, in terms of mass percentage. The nano modifier is preferably nano silicon dioxide and nano aluminum oxide; the particle size of the nano silicon dioxide is 10-100nm; the particle size of the nano aluminum oxide is 20-200nm.

[0040] In the present invention, the alkaline activator preferably comprises 10-15% sodium silicate solution, 25-30% sodium hydroxide and 60% water; more preferably 12-14% sodium silicate solution, 26-28% sodium hydroxide and the balance water, and the mass concentration of the sodium silicate solution is preferably 5-20%, more preferably 10-15%.

[0041] In the present invention, the method for preparing the nano inorganic resin preferably comprises: grinding lithium slag, adding a nano modifier and an alkali activator in sequence, and dissolving them to obtain the nano inorganic resin.

[0042] In the present invention, the grinding is preferably performed until the particle size of the lithium slag is 1200 meshes.

[0043] In the present invention, the dissolution pressure is preferably 0.3 MPa, the temperature is preferably 250° C., and the time is preferably 8 to 10 hours, more preferably 9 to 10 hours.

[0044] Based on the total mass fraction of the liquid component being 100%, the liquid component comprises 0.5-1%, more preferably 0.75-0.90% of the coupling agent. The coupling agent is preferably aminosilane powder; the particle size of the aminosilane powder is preferably 1200-2000 meshes.

[0045] Based on the total mass fraction of the liquid component of 100%, the liquid component includes 1.5-2.5% of the lanthanum-cerium rare earth salt, more preferably 1.8-2.2%, and further preferably 2.0%; the lanthanum-cerium rare earth salt preferably includes lanthanum chloride and cerium chloride, the mass ratio of lanthanum chloride to cerium chloride is preferably 2-3:1, and the particle size of the lanthanum-cerium rare earth salt is preferably 400-600 mesh.

[0046] Based on the total mass fraction of the liquid component of 100%, the liquid component includes 0.1-0.2% of nano yttrium powder, and more preferably 0.15%; the nano yttrium powder preferably includes yttrium oxide; the purity of the nano yttrium powder is preferably 99.99%, and the particle size is preferably 50-100nm.

[0047] The solidified lepidolite slag cementitious material provided by the present invention comprises 65-80% of a powder component, more preferably 70-75%; based on the total mass fraction of the powder component being 100%, the powder component comprises 30-35% of high-calcium fly ash, more preferably 32-34%, the calcium content of the high-calcium fly ash is preferably greater than 25wt%, and the particle size is 5000-8000 mesh.

[0048] Based on the total mass fraction of the powder component of 100%, the powder component includes 40-45% of high calcium slag powder, more preferably 42-44%, and the high calcium slag powder is preferably obtained by grinding 95 slag powder; the calcium content of the high calcium slag powder is preferably 10-30wt%, more preferably 15-20wt%, and the particle size is preferably 5000-8000 mesh. The present invention has no special restrictions on the source and composition of the 95 slag powder, and the 95 slag powder of a source well known in the art can be used.

[0049] Based on the total mass fraction of the powder component of 100%, the powder component includes 8-16% saw mud, more preferably 10-15%, and further preferably 12-13%. The saw mud is obtained by grinding granite, and the particle size of the saw mud is preferably 5000-8000 mesh. The present invention has no special limitation on the source and composition of the granite, and granite from sources well known in the art can be used.

[0050] Based on the total mass fraction of the powder component of 100%, the powder component includes 8-16% brick powder, more preferably 10-15%, and further preferably 12-13%; the brick powder is obtained by grinding red-based bricks, and the particle size of the brick powder is preferably 5000-8000 mesh; the red-based bricks of the present invention are preferably red-based bricks discarded from construction waste.

[0051] Based on the total mass fraction of the powder component being 100%, the powder component comprises 1 to 1.5% of a water reducer, more preferably 1.2 to 1.3%; the water reducer is preferably a naphthalene-based water reducer; and the naphthalene-based water reducer is preferably a naphthalenesulfonate-type water reducer.

[0052] The present invention has no special limitation on the preparation method of the solidified lithium mica slag cementitious material, and the liquid component and the powder component are mixed and stirred for 3 to 5 minutes according to the required raw material ratio. During the mixing and stirring process, the liquid component and the powder component undergo an alkali excitation reaction under the action of rare earth salts. The reaction principle is that the raw materials containing (aluminum) silicate minerals (fly ash, slag powder, saw mud, brick powder) release silicon and aluminum monomers under the action of an alkali activator solution, and the silicon and aluminum monomers are then modified by polymerization and rare earth salts in the solution to form a colloid with nano-micropores, which is mixed with lithium slag that needs to lock beryllium and thallium, and maintained at room temperature. Finally, the aluminum silicate particles are connected to form nano-pores and channels under the action of rare earth elements to lock heavy metal elements to form a strength body, that is, a cementitious material.

[0053] The present invention provides the application of the solidified lepidolite slag cementitious material in the above technical solution in building materials. The present invention has no special limitation on the application method, and the cementitious material can be used as a strength body in building materials according to methods well known in the art.

[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0055] Example 1

[0056] The solidified lepidolite slag gel material provided in this embodiment comprises 20% of liquid component and 80% of powder component;

[0057] Based on a total mass fraction of 100%, the liquid component comprises: 97.0% of nano inorganic resin, 0.75% of coupling agent, 2.0% of lanthanum cerium rare earth salt and 0.15% of nano yttrium powder;

[0058] Preparation of the nano inorganic resin: Grind lithium slag to a particle size of 1200 meshes, pour into an autoclave, add a nano modifier and an alkali activator in sequence, pressurize the autoclave to 0.3 MPa, react at 250° C. for 10 hours, and obtain the nano inorganic resin; wherein the raw materials have a mass percentage of 40% lithium slag, 5% nano modifier, and 55% alkali activator;

[0059] The nano modifiers are nano silicon dioxide and nano aluminum oxide; the mass ratio of the nano silicon dioxide to the nano aluminum oxide is 3:7; the particle size of the nano silicon dioxide is 10 to 100 nm; the particle size of the nano aluminum oxide is 20 to 200 nm;

[0060] The alkaline activator comprises 12% sodium silicate solution, 28% sodium hydroxide and 60% water; the mass concentration of the sodium silicate solution is 10%;

[0061] The coupling agent is aminosilane powder, and the particle size of the aminosilane powder is 1200-2000 mesh;

[0062] The lanthanum-cerium rare earth salt preferably includes lanthanum chloride and cerium chloride, the mass ratio of the lanthanum chloride to the cerium chloride is 2:1, and the particle size of the lanthanum-cerium rare earth salt is 400-600 mesh;

[0063] The nano yttrium powder is yttrium oxide, the purity of yttrium oxide is preferably 99.99%, and the particle size is 50-100nm;

[0064] Based on a total mass fraction of 100%, the powder components include: 32% high-calcium fly ash, 42% high-calcium slag powder, 12% sawdust, 12% brick powder and 1.2% water reducer;

[0065] The high calcium fly ash has a calcium content of >25wt% and a particle size of 5000-8000 mesh;

[0066] The high calcium slag powder is obtained by grinding 95 slag powder to 5000-8000 mesh; the calcium content of the 5000-8000 mesh high calcium slag powder is 20wt%;

[0067] The saw mud is made by grinding granite to 5000-8000 mesh;

[0068] The brick powder is obtained by grinding abandoned red-based bricks from construction waste to 5000-8000 meshes;

[0069] The water reducer is a naphthalene-based water reducer, a naphthalenesulfonate-type water reducer;

[0070] Preparation method of gelling material: Mix and stir the corresponding raw material components for 5 minutes to obtain the gelling material.

[0071] Example 2

[0072] The only difference from Example 1 is:

[0073] The gelling material provided in this embodiment includes a liquid component and a powder component;

[0074] Based on a total mass fraction of 100%, the liquid component comprises: 96.3% of nano inorganic resin, 0.5% of coupling agent, 1.5% of lanthanum cerium rare earth salt and 0.1% of nano yttrium powder;

[0075] Based on a total mass fraction of 100%, the powder components include: 30% high-calcium fly ash, 40% high-calcium slag powder, 8% sawdust, 8% brick powder and 1% water reducer;

[0076] The rest is the same as in Example 1.

[0077] Example 3

[0078] The only difference from Example 1 is:

[0079] The gelling material provided in this embodiment includes a liquid component and a powder component;

[0080] Based on a total mass fraction of 100%, the liquid component comprises: 97.9% of nano inorganic resin, 1% of coupling agent, 2.5% of lanthanum cerium rare earth salt and 0.2% of nano yttrium powder;

[0081] Based on a total mass fraction of 100%, the powder components include: 35% high-calcium fly ash, 45% high-calcium slag powder, 16% sawdust, 16% brick powder and 1.5% water reducer;

[0082] The rest is the same as in Example 1.

[0083] Characterization and performance testing

[0084] 1) Figure 1 This is the SEM image of the gelling material prepared in Example 1. Figure 1 It can be seen that the 5nm to 20nm aluminosilicate particles are connected into nanopores and channels under the action of rare earth elements.

[0085] 2) The long-term performance and durability of the cementitious material prepared in Example 1 were tested according to standard GB / T50082. The results are shown in Table 1.

[0086] Table 1 Performance data of the cementitious material of Example 1

[0087] Cementitious materials Compressive strength grade C40 Flexural strength 7MPa Freeze-thaw resistance grade D200 Impermeability grade P20

[0088] It can be seen from Table 1 that the cementitious material provided by the present invention has excellent performance and can be used as an excellent green building material.

[0089] 3) Figures 2-3 The test results of the raw lithium slag and the cementitious material of Example 1 are as follows; Figures 2-3 It can be seen that the curing effect of harmful elements such as beryllium and thallium in the gelling material of the present invention is above 99%.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A solidified lepidolite slag cementitious material, characterized in that: Based on the total mass fraction of 100%, it includes 20-35% of independently packaged liquid components and 65-80% of powder components; Based on the total mass fraction of the liquid component being 100%, the liquid component comprises: 96.3-97.9% of nano inorganic resin, 0.5-1% of coupling agent, 1.5-2.5% of lanthanum cerium rare earth salt and 0.1-0.2% of nano yttrium powder; Based on the total mass fraction of the powder components being 100%, the powder components include: 30-35% high-calcium fly ash, 40-45% high-calcium slag powder, 8-16% sawdust, 8-16% brick powder and 1-1.5% water reducer; The raw materials for preparing the nano inorganic resin include lithium slag, nano modifier and alkali activator; Based on a total mass fraction of 100%, the raw materials for preparing the nano inorganic resin include 40-60% lithium slag, 5-10% nano modifier and 30-55% alkali activator; In terms of mass percentage, the nano modifier includes 10-30% of nano silicon dioxide and 70-90% of nano aluminum oxide; The preparation method of the nano inorganic resin comprises: grinding lithium slag, adding a nano modifier and an alkali activator in sequence, dissolving them, and obtaining the nano inorganic resin; The dissolution pressure is 0.3 MPa, the temperature is 250° C., and the time is 8 to 10 hours.

2. The solidified lepidolite slag cementitious material according to claim 1, wherein The alkali activator comprises 10-15% of sodium silicate solution, 25-30% of sodium hydroxide and 60% of water.

3. The solidified lepidolite slag cementitious material according to claim 1, characterized in that The grinding is performed until the particle size of the lithium slag is 1200 meshes.

4. The solidified lepidolite slag cementitious material according to claim 1, characterized in that The coupling agent is aminosilane powder, and the particle size of the aminosilane powder is 1200-2000 mesh; The lanthanum-cerium rare earth salt comprises lanthanum chloride and cerium chloride, the mass ratio of the lanthanum chloride to the cerium chloride is 2-3:1, and the particle size of the lanthanum-cerium rare earth salt is 400-600 meshes; The nano yttrium powder comprises yttrium oxide; the purity of the nano yttrium powder is 99.99% and the particle size is 50-100nm.

5. The solidified lepidolite slag cementitious material according to claim 1, characterized in that The high calcium fly ash has a calcium content of >25wt% and a particle size of 5000-8000 mesh; The high calcium slag powder is obtained by grinding 95 slag powder; the calcium content of the high calcium slag powder is 10-30wt%, and the particle size is 5000-8000 mesh; The saw mud is obtained by grinding granite, and the particle size of the saw mud is 5000-8000 mesh; The brick powder is obtained by grinding red base brick, and the particle size of the brick powder is 5000-8000 mesh; The water reducer is a naphthalene-based water reducer.

6. Application of the solidified lepidolite slag cementitious material according to any one of claims 1 to 5 in building materials.

Citation Information

Patent Citations

  • Nano inorganic gel modifier and preparation method thereof

    CN113955976A

  • Lithium slag-based early-strength and high-strength cementing material and preparation method thereof

    CN115893888A